2015
DOI: 10.1039/c5fo00510h
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient values and bioactivities of the extracts from three fern species in China: a comparative assessment

Abstract: Pteridium aquilinum, Osmunda cinnamomea Linn, and Athyrium multidentatum (Doll.) Ching are three fern species widely consumed as potherbs and traditional medicinal herbs in China. Nevertheless, no detailed comparative assessments of their nutrient values and bioactivities have been reported. In this paper, we examined the nutrient content of these ferns and the bioactivities of their extracts with a comparative method. The results indicated that they were nutrient dense for proteins, carbohydrates, fat and min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Previous studies demonstrated that AMC could substantially suppress mitochondria membrane potential (MMP) 10 . As the early stage of intrinsic apoptosis, loss of MMP could induce cytochrome c releasing into cytosol from mitochondria membrane and activating caspase cascade and PARP cleavage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that AMC could substantially suppress mitochondria membrane potential (MMP) 10 . As the early stage of intrinsic apoptosis, loss of MMP could induce cytochrome c releasing into cytosol from mitochondria membrane and activating caspase cascade and PARP cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…AMC extracts possessed a strong antioxidant activity, protective effects on biomolecules, cellular antioxidant activity (CAA), and anti-proliferative effects owing to its highest total phenolic (476.52 ± 11.26 mg GAE per gram extract) and total flavonoid (924.81 ± 4.25 mg RNE per gram extract) contents. Furthermore, AMC extracts exhibited a promising effect on the inhibition of cell proliferation and stimulated apoptosis in HepG2 cancer cells 10 . However, the underlying molecular mechanisms of AMC-induced apoptosis in HepG2 cells remain elusive.…”
Section: Introductionmentioning
confidence: 98%
“…After treatment, cells were stained with JC‐1 of l0 μg /mL for 30 min at 37 °C in the dark. Then cells were washed with PBS twice and measured by a microplate reader (Molecular Devices Co., Sunnyvale, CA) with settings of FL1 (green) at 538 nm and FL2 (red) at 585 nm …”
Section: Methodsmentioning
confidence: 99%
“…The results were reported as the mg gallic acid equivalents (GAE)/g dry weight (DW). Total flavonoid (TF) content was determined using the slightly modified method (Qi et al, 2015). The total flavonoid concentration was calculated from a calibration curve using rutin as the standard (0-400 mg L À1 ).…”
Section: Determination Of Total Polyphenols and Total Flavonoidsmentioning
confidence: 99%